Efektivitas Terapi Musik dalam Menurunkan Ansietas pada Pasien yang Dirawat di Ruang Intensif - A N Dahlia Sinambela; Dewi Irawati; Riri Maria (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the effectiveness of music therapy in reducing anxiety in patients treated in the intensive care unit. The method used is a literature review design, a scientific article literature review conducted to answer predetermined research questions. A search for articles was carried out in a structured manner in November 2022 through an online database, including using predefined keywords, namely "(intensive care OR critical care) AND (music therapy OR music intervention OR listening music) AND (anxiety)". The databases used are Sciendirect, Proquest, Sagejournal, and Pubmed, using predefined keywords. The results of the study show that music therapy is effective in reducing anxiety in patients who are treated in the intensive care unit. Conclusion: Music therapy effectively reduces stress in patients treated in the intensive care unit, which needs to be developed and used as a non-pharmacological intervention in the future to reduce anxiety in patients treated in the intensive care unit. Keywords: Anxiety, Intensive Room, Critical Care, Music Therapy